Voluntary hypoventilation at low lung volume (VHL) during strength and conditioning training increases anaerobic performance: A pilot study - Hundley, Z. (Liberty University, 2020)
To determine whether a VHL protocol implemented into an already existing strength and conditioning program could improve anaerobic conditioning more efficiently within the military population. Six active duty males completed a seven-week training cycle with VHL protocols implemented on each training day (2-4 days/week). Before (Pre) and after (Post) protocol implementation, the participants performed a multi-stage 20-m shuttle run test (MSRT). After incorporating VHL, participants significantly improved their MRST scores by an average of 50.3%. Additionally, Body Oxygen Level Test (BOLT) scores were improved across the duration of the study. This study showed employing VHL can improve anaerobic performance in the MSRT within the military population. Given the need for training efficiency, utilizing VHL could provide a safe and cost-effective training stimulus to improve anaerobic performance.